Efficient Plant Production of Recombinant NS1 Protein for Diagnosis of Dengue - Mariana Fonseca Xisto; Roberto Sousa Dias; Elias Feitosa-Araujo; John Willians Oliveira Prates; Cynthia Canedo da Silva; Sérgio Oliveira de Paula (Frontiers in Plant Science, 2020)
Dengue fever is endemic in more than 120 countries, which account for 3.9 billion people at risk of infection worldwide. The absence of a vaccine with effective protection against the four serotypes of this virus makes differential molecular diagnosis the key step for the correct treatment of the disease. Rapid and efficient diagnosis prevents progression to a more severe stage of this disease. Currently, the limiting factor in the manufacture of dengue (DENV) diagnostic kits is the lack of large-scale production of the non-structural 1 (NS1) protein (antigen) to be used in the capture of antibodies from the blood serum of infected patients. In this work, we use plant biotechnology and genetic engineering as tools for the study of protein production for research and commercial purposes. Gene transfer, integration and expression in plants is a valid strategy for obtaining large-scale and low-cost heterologous protein production. The authors produced NS1 protein of the dengue virus serotype 2 (NS1DENV2) in the Arabidopsis thaliana plant. Transgenic plants obtained by genetic transformation expressed the recombinant protein that was purified and characterized for diagnostic use. The yield was 203 μg of the recombinant protein per gram of fresh leaf. By in situ immunolocalization, transgenic protein was observed within the plant tissue, located in aggregates bodies. These antigens showed high sensitivity and specificity to both IgM (84.29% and 91.43%, respectively) and IgG (83.08% and 87.69%, respectively). The study goes a step further to validate the use of plants as a strategy for obtaining large-scale and efficient protein production to be used in dengue virus diagnostic tests.